English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

subtract 5m^2+2m+9 from 7m^2-5m-8

simplify (m^4)^3(m^2)^9/(m^3)^2

2007-10-07 12:42:27 · 3 answers · asked by tricey7578 2 in Science & Mathematics Mathematics

3 answers

(7m^2-5m-8) - (5m^2+2m+9)
=7m^2-5m-8-5m^2-2m-9
2m^2-7m-17

(m^4)^3(m^2)^9/(m^3)^2
=m^12*m^18/m^6
=m^30/m^6
=m^24

2007-10-07 12:47:22 · answer #1 · answered by Wooly 4 · 0 0

subtract 5m^2+2m+9 from 7m^2-5m-8
7m^2-5m-8
-(5m^2+2m+9) = - 5m^2 - 2m - 9
-------
2m^2 - 7m - 17


simplify (m^4)^3(m^2)^9/(m^3)^2
(m^4)^3 = m^12 (just multiply 4*3)
(m^2)^9 = m ^18 (just multiply 2*9)
(m^3)^2 = m^6 (multiply 3*2)

m^12*m^18 / m^6 = m^24 (add 12 + 18 and subtract 6)

2007-10-07 12:48:44 · answer #2 · answered by Steve A 7 · 0 0

(7m^2-5m-8)-(5m^2+2m+9)
=7m^2-5m-8-5m^2-2m-9
=2m^2-7m-17

(m^4)^3(m^2)^9/(m^3)^2
=(m^12)(m^18)/(m^6)
=m^24

2007-10-07 12:50:34 · answer #3 · answered by slick_licker88 3 · 0 0

fedest.com, questions and answers